Competitive transport, extraction and coordination chemistry of a number of ligands with selected transition and post-transition metal ions - Sheng, Xia (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--Stellenbosch University, 2008.